Dispersed Organic Matter of the Severo-Novoborskaya Parametric Well - G. L. Belyaeva; I. S. Khopta (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2023)
The study of dispersed organic matter in the section of the Severo-Novoborskaya parametric well (south of the Nenets Autonomous Area) made it possible to reveal its genesis, maceral composition, and secondary changes. Obtained information allowed reconstructing and the catagenetic zoning of the section, determining the position of the lower boundary of oil occurrence, the main zones of oil and gas generation.